Occurrence of Methicillin-Resistant Staphylococcus aureus (MRSA) in Bovine Bulk Milk and Farm Workers in Smallholder Dairy Farming Systems in Northwestern Ethiopia - Kassa HY; Belete MA; Yihunie FB; Bayu A; Demlie TB; Tassew H (Veterinary Medicine: Research and Reports, 2024)
Haregua Yesigat Kassa,1 Mequanint Addisu Belete,1 Fanuel Bizuayehu Yihunie,2 Azeb Bayu,3 Tiliksew Bialfew Demlie,4 Habtamu Tassew4 1Department of Veterinary Laboratory Technology, College of Agriculture and Natural Resource, Debre Markos University, Debre Markos, Ethiopia; 2College of Veterinary Medicine and Animal Science, Samara University, Samara, Ethiopia; 3Department of Veterinary Science, College of Agriculture and Environmental Science, Debre Tabor University, Debre Tabor, Ethiopia; 4Department of Veterinary Science, College of Agriculture and Environmental Sciences, Bahir Dar University, Bahir Dar, EthiopiaCorrespondence: Mequanint Addisu Belete, Email mequanentaddisu@gmail.com; mequanint_addisu@dmu.edu.etBackground and Purpose: Staphylococcus aureus is a common pathogen responsible for causing various human and animal infections and is well known for its ability to develop resistance to multiple antibiotics. This study aimed to evaluate the occurrence of methicillin-resistant Staphylococcus aureus (MRSA) in bulk milk and dairy farms in northwestern Ethiopia and to determine their phenotypic and genotypic antimicrobial susceptibility patterns.Methods: We collected 50 bulk milk samples from 50 dairy farms and 50 hand swabs from dairy milkers. The cefoxitin disk diffusion test and PCR-based assays were used to identify MRSA isolates. In addition, cefoxitin-resistant isolates were tested for susceptibility to other antibiotics using the Kirby-Bauer disk diffusion method.Results: The results showed that MRSA was detected in 8 samples: 6 from bulk milk samples (12%) and 2 from hand swabs (4%). All MRSA isolates exhibited a high resistance rate to penicillin (100%), followed by tetracycline (75%), ciprofloxacin (25%), chloramphenicol (25%), erythromycin (25%), gentamycin (12.5%), and trimethoprim-sulfamethoxazole (12.5%). Moreover, 72% of the isolates showed resistance to three or more antibiotic classes and were classified as multidrug-resistant.Conclusion: This study identified methicillin-resistant Staphylococcus aureus and multidrug-resistant MRSA in bulk milk and dairy farms in northwestern Ethiopia. These findings highlight the potential risk of transmission of these antibiotic-resistant bacteria to humans and the need for improved antibiotic stewardship in the dairy sector using the One Health approach.Keywords: dairy farms, Ethiopia, humans, MRSA, bulk milk, resistance